Dependency of energy loss on strain rate, strain magnitude and preload: Towards development of a novel biomarker for aortic aneurysm dissection risk. (December 2021) - Tang, Mingyi; Eliathamby, Daniella; Ouzounian, Maral; Simmons, Craig A.; Chung, Jennifer C.-Y
Abstract: Dissection is the most common mode of failure for ascending aortic aneurysms. Currently, failure risk is assessed by measuring aortic diameter, which is insufficient as it misses many dissection patients. This motivated the search for a new biomarker that captures intrinsic tissue material properties related to failure. Energy loss is promising in this regard as it is correlated with microstructure degradation and failure of aneurysms. However, for energy loss to be used clinically, its dependency on in vivo loading conditions, which vary from patient-to-patient, must be determined. In this study, the sensitivity of energy loss to physiological strain rate, magnitude, and preload was examined. Energy loss was found to be relatively insensitive to loading conditions while maintaining a significant correlation with delamination strength as a surrogate for dissection except at low strains. These results can be used for clinical translation of in vivo measurements of energy loss to evaluate aortic dissection risk.